Sociolinguistic and Extralinguistic Aspects of the Functioning of the Trilingualism in the Oil Industry of Kazakhstan - Кулпаш Коптлеуова; Балгенже Карагулова; Багіла Муратбек; Майрагул Куштаєва; Кулшат Кондибай (Психолінгвістика)
The purpose of the research. This paper describes the linguistic situation in the oil industry of Kazakhstan. The linguistic situation in the oil industry of Kazakhstan is characterized by functioning of the trilingualism with three languages being used simultaneously – Kazakh, Russian and English.